Challenges of HIV diagnosis and management in the context of pre‐exposure prophylaxis (PrEP), post‐exposure prophylaxis (PEP), test and start and acute HIV infection: a scoping review. Issue 12 (18th December 2019) - Elliott, Tamara; Sanders, Eduard J; Doherty, Meg; Ndung'u, Thumbi; Cohen, Myron; Patel, Pragna; Cairns, Gus; Rutstein, Sarah E; Ananworanich, Jintanat; Brown, Colin; Fidler, Sarah
Abstract: Introduction: Knowledge of HIV status relies on accurate HIV testing, and is the first step towards access to HIV treatment and prevention programmes. Globally, HIV‐status unawareness represents a significant challenge for achieving zero new HIV infections and deaths. In order to enhance knowledge of HIV status, the World Health Organisation (WHO) recommends a testing strategy that includes the use of HIV‐specific antibody point‐of‐care tests (POCT). These POCTs do not detect acute HIV infection, the stage of disease when viral load is highest but HIV antibodies are undetectable. Complicating things further, in the presence of antiretroviral therapy (ART) for pre‐exposure prophylaxis (PrEP) or post‐exposure prophylaxis (PEP), other currently available testing technologies, such as viral load detection for diagnosis of acute HIV infection, may yield false‐negative results. In this scoping review, we evaluate the evidence and discuss alternative HIV testing algorithms that may mitigate diagnostic dilemmas in the setting of increased utilization of ART for immediate treatment and prevention of HIV infection. Discussion: Missed acute HIV infection prevents people living with HIV (PLHIV) from accessing early treatment, increases likelihood of onward transmission, and allows for inappropriate initiation or continuation of PrEP, which may result in HIV drug resistance. While immediate ART is recommended for all PLHIV, studies have shown that starting ART in the setting of acute HIV infection may result in a delayed or complete absence of development of HIV‐specific antibodies, posing a diagnostic challenge that is particularly pertinent to resource‐limited, high HIV burden settings where HIV‐antibody POCTs are standard of care. Similarly, ART used as PrEP or PEP may supress HIV RNA viral load, complicating current HIV testing algorithms in resource‐wealthy settings where viral detection is included. As rollout of PrEP continues, HIV testing algorithms may need to be modified. Conclusions: With increasing use of PrEP and ART in acute infection we anticipate diagnostic challenges using currently available HIV testing strategies. Research and surveillance are needed to determine the most appropriate assays and optimal testing algorithms that are accurate, affordable and sustainable.